Informing Policy and Practice Through Assessment of New Library Books' Usage at Makerere University. Issue 3 (2nd April 2017) - Musoke, Maria G. N.; Mwesigwa, Andrew
Abstract : Makerere University Library procured 11, 811 copies (4, 662 titles) of the latest editions of textbooks with funding from Carnegie Corporation of New York. By the time of the study, there were 20, 251 titles in both International Development Agency and Law textbook sections of the main library, of which 23% were the newly acquired titles. The books were selected by lecturers from all academic departments. Prior to the selection, lecturers were trained in modern book selection methods to ensure that they made appropriate selections and updated the reading lists. Once received, the bibliographic records of new books were entered in the Virtua Integrated Library System. After 1 year, Makerere University Library conducted a study to find out whether the new books were being used, how relevant the books were to users' needs, whether the reading lists were current, whether user education, library catalogues, etc., had any influence on the usage of new books. The first set of data was electronically collected for 2 weeks during the peak period (11th and 12th weeks of the semester) using the Virtua Integrated Library System circulation module. While the second set of data was collected in the 5th and 7th weeks of the semester both electronically and manually to address the gaps realized in the first set of data that was collected only electronically. A short, self-administered questionnaire was used to manually collect data; it had 10 questions, two of which were open-ended. The quantifiable data was analyzed using Google spreadsheets, while the qualitative data was categorized into themes. The findings indicated that the books were overwhelmingly relevant (95%); while 93% of the respondents identified the new books from the reading lists, confirming that the lists had been updated and hence the book selection training was timely. Course mates contributed 30%, online catalogue 14%, while library user education (20%) and other information literacy training sessions contributed to raising awareness about the new books and the sections where they are located. The article concludes by highlighting the implications of the study findings for policy and practice, lessons learned, as well as identifying areas in library services at Makerere University Library that require further research.